Gall bladder ejection fraction as a marker of autonomic neuropathy in type 2 diabetes mellitus - Kalyani, D. Vasantha; Sheela, P. R.; Kumar, P. Suresh; Nagalingam, Saranya (International Journal of Research in Medical Sciences, 2019)
Background: Diabetic neuropathy is one of the commonest complications of diabetes mellitus and associated with considerable morbidity and mortality. The influence of diabetes on gall bladder function was not demonstrated in many studies. In this study, the association of fasting gall bladder volume and gall bladder ejection fraction with degree of cardiac autonomic neuropathy was assessed and correlated with duration of diabetes and severity of diabetes.. Methods: The study was conducted in Government Sivagangai Medical College Hospital, Sivagangai, Madurai during a period of January 2018 to September 2018 as a Prospective observational study conducted among 100 patients in study group and 50 healthy subjects in control group. The aim of the study was to find out the incidence of autonomic neuropathy in study group by simple bed side tests, to determine the fasting gall bladder ejection fraction in diabetics, comparison of gall bladder volume in both study and control group, correlation of gall bladder ejection fraction with autonomic neuropathy. Results: The incidence of CAN is found to be high with longer duration of the disease and the degree is also correlated with duration of the disease. The correlation coefficient of this association is 0.792 which indicates high correlation. The correlation of severity of DM with incidence and degree of CAN was 0.81 which indicates high correlation and also the study showed an increase in the FGBV and a decrease in the GBEF with increase in the severity of cardiac autonomic neuropathy. Conclusions: In patients with type 2 diabetes mellitus, the gall bladder ejection fraction is significantly related to the duration of diabetes mellitus and degree of hyperglycemia in addition to cardiac autonomic neuropathy(CAN). Similarly, fasting gall bladder volume (FGBV) is significantly increased in type 2 diabetes mellitus patients with cardiac autonomic neuropathy.